Masquerade Queer Poetry in America to the End of World War II - Elledge, Jim (Indiana University Press, 2003)
Masquerade is the most comprehensive anthology yet published of poetry by American gays, lesbians, bisexuals, and transgendered persons. It includes representative poems from more than 100 writers from pre-colonial times to the end of the Second World War. The anthology begins with selections of anonymous texts from the oral traditions of Hawaii and Native America, followed by voodoo chants and cowboy songs (with a few limericks thrown in for good measure). The selections are arranged by the year of the poet's birth and include samplings of poetry by a racially and ethnically diverse group of men and women. Contemporary readers will know the work of some of these poets, such as Gertrude Stein and Walt Whitman. Other poets, such as George Santayana and Adah Isaacs Menken, will be strangers to most. In all, these poets created a rich heritage of verse that has been for the most part masked throughout the history of American literature.